PHENOLOGICAL WATER BALANCE APPROACH FOR THE DETERMINATION OF OPTIMUM SOWING DATES FOR MAYA MAIZE (Zea mays) IN A FOREST-SAVANNA TRANSITION ZONE OF NIGERIA - Makinde, A.A.; Adetona, A.I.; Eruola, A.O.; Bello, N.J. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study determined the preparatory period, rain onset, and the sowing period limit, it also assessed the planting dates in relation to growth parameters and evaluated the effects of the planting date on grain yield of Egun maize. This research used an agroclimatological water balance method based on rainfall and potential evapotranspiration (P – PE) model to find the best time to plant Maya maize (Zea mays) in Abeokuta. Three planting dates derived from the (P – PE) model were used: D1(April 27) when the accumulated difference between rainfall and half potential evapotranspiration was zero (ƩP-0.5PE = 0): D2 (May 4) when ƩP-0.5PE = 6mm: and D3 (May 11) when ƩP-0.5PE= 10mm. The Maya maize was planted in a randomized complete block design with three replicates. Data collected were subjected to analysis of variance(ANOVA) and means were separated using LSD. Result showed that the optimum planting dates of Maya maize was April 27, with yield of about 3229.17 kg/ha. Planting dates had no significant effects (p>0.05) on the growth parameters of Maya maize. The schedule of farm operations for maize cultivation showed that, land preparation should commence as soon as the accumulated difference between P and 0.5PE approaches zero while ridging and planting could be done simultaneously. The variability of rainfall is not limited to extreme condition of wetness due to prolong wet spells and loss of soil nutrients might increase with higher accumulated difference between P and 0.5PE, this implies that early planting of Egun maize is encouraged to improve yield due to higher nutrients availability at the early dates of sowing. The study concluded, that planting Maya maize around April 27 optimizes grain yield by ensuring better nutrient availability and reducing the risk of nutrient loss due to prolonged wet spells.